Idiom dalam Masyarakat Pondek Tengah Kecamatan Limo Koto Kabupaten Muko-muko Bengkulu Utara - Harlina, Harlina; Juita, Novia; Emidar, Emidar (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
The purpose of this article is (1) to describe the form of idioms in English cottage Central District V Koto Muko-Muko district of North Bengkulu, (2) describe the meaning of idioms in English cottage Central District V Koto Muko-Muko district of North Bengkulu, (3) describe the function of idiom in the language of the Middle District V Koto cottage Muko-Muko district of North Bengkulu. This research is a qualitative study using descriptive methods. The findings of the study are (1) the idioms used by the Central Cottage Village Community in the form of two words and three words, (2) the meaning of idioms in the group by stating the nature, naming, and daily activities, (3) function idiom to quip, praise, express anger, expressed his joy/love and, expressed his sadness.